COVID-19 health crisis and prevalence of anxiety among individuals of various age groups: a qualitative study. Issue 1 (18th November 2020) - Ahmed, Ammar; Aqeel, Muhammad; Aslam, Naeem
Abstract : Purpose: The monetary and psycho-social ramifications of the COVID-19 pandemic have been extensive and unimaginable around the globe. The purpose of this study was to have a psycho-social analysis of people confronting this situation and its impact in the situation of a health crisis on them. Design/methodology/approach: In the current study, participants were divided according to their different backgrounds and professions based on the types of measures taken by the Pakistani government to limit the spread of the virus and people who are not disturbed by any of the measurement categories but are troubled by the coronavirus. The interviews based on five open-ended questions were conducted with the eight participants, comprising questions that helped participants in remembering and realizing the purpose of the interview in the mode of an open questioning. Phenomenological interpretative analysis was used to understand how participants make meaning of the phenomenon being studied, an in-depth analysis of the human subject was considered in its singularity, and personal accounts and experiences were noted regarding this pandemic. Findings: The results indicated that the participant's experiences were marked by stress, insecurity, anger, fear, anxiety, traces of painful emotions and a feeling of weakness. Also the prevalence of unknown precariousness and vulnerability of coronavirus aggravated the psychological frailness among people existing in an anxiety-prone situation created by the novel coronavirus. Confronted with these painful experiences, the participants however, used a variety of cognitive and behavioral efforts which needs to be strengthened by psychological care. Research limitations/implications: This study based on qualitative method was performed on diverse socio-professional levels, giving an insight to what they are undergoing, their current fears, desires and their feeling. The outcome of this study reveals traces of uncertainty, anxiety, fears, insecurity and hidden imminent death from coronavirus, therefore highlighting a need for immediate psychological interventions. Originality/value: This study explores the individual understanding regarding current coronavirus pandemic situation on subjective lived experiences and psychological health in an anxiety-prone context manifested by the health crisis created by the novel corona virus.